Cytomegalovirus‐induced thrombotic microangiopathy after renal transplant successfully treated with eculizumab: case report and review of the literature. (24th April 2015) - Java, Anuja; Edwards, Angelina; Rossi, Ana; Pandey, Richa; Gaut, Joseph; Delos Santos, Rowena; Miller, Brent; Klein, Christina; Brennan, Daniel
Summary De novo thrombotic microangiopathy (TMA) after renal transplant is rare. Cytomegalovirus (CMV)‐related post‐transplant TMA has only been reported in 6 cases. We report an unusual case of a 75‐year‐old woman who developed de novo TMA in association with CMV viremia. The recurrence of TMA with CMV viremia, the resolution with treatment for CMV, and the lack of correlation with a calcineurin inhibitor (CNI) in our case support CMV as the cause of the TMA. What is unique is that the use of eculizumab without plasmapheresis led to prompt improvement in renal function. After a failure to identify a genetic cause for TMA and the clear association with CMV, eculizumab was discontinued. This case provides insight into the pathogenesis and novel treatment of de novo TMA, highlights the beneficial effects of complement inhibitors in this disease, and shows that they can be safely discontinued once the inciting etiology is addressed.